Tell tale [compact disc, unabridged] : stories - Archer, Jeffrey, 1940- (Macmillan Audio, 2017)
In this collection of short stories, Archer gifts us with a dozen different tales ranging from murder mysteries to bildungsromans to war stories based on real events that have critics comparing him to Dumas, Dahl, and Maugham.